2004
DOI: 10.1073/pnas.0308368101
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-induced maturation of dendritic cells through a PI3 kinase-mediated TNF-α induction pathway

Abstract: Systemic administration of adenovirus and adenovirus vectors induces a robust innate and adaptive immune response in a variety of animal models. In tumor necrosis factor (TNF) ؊/؊ mice, a diminished immune response to adenovirus (Ad) infection has been attributed to compromised dendritic cell (DC) maturation. In this report, we investigated the mechanisms responsible for Ad-mediated activation and maturation of DC. Ad infection induced high levels of ⌻NF-␣ expression by murine bone marrow-derived DC, comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
88
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 47 publications
9
88
1
Order By: Relevance
“…The innate immune receptor to the Ad has not yet been identified. It has not even been determined whether TLRs are involved in Ad-mediated innate immune response in vivo, although it has been reported that TLR signals are not involved in the DC maturation induced by the Ad vector (46). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The innate immune receptor to the Ad has not yet been identified. It has not even been determined whether TLRs are involved in Ad-mediated innate immune response in vivo, although it has been reported that TLR signals are not involved in the DC maturation induced by the Ad vector (46). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increased cytokine/chemokine production after the injection of Ad vectors has been reported to be due to the introduction of input Ad vectors to Kupffer cells in the liver and DC (15,17,(43)(44)(45)(46). Detailed analysis of the organs responsible for the expression of cytokines, chemokines, and IFNs by RT-PCR suggests that their production can mainly be attributed to spleen cells (especially splenic conventional DC), not liver cells (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…All TLRs are capable of signaling through the adaptor molecule MyD88, which has been shown to be nonessential for AdHu5 vector-induced DC maturation (17). Some TLRs, such as TLR3 and TLR4, can also signal independently of MyD88 (18).…”
Section: Ad-induced Type I Ifn Does Not Require Viral Transcription mentioning
confidence: 99%
“…Ad vectors efficiently transduce and express transgene in DCs (10 -12); however, viral gene expression is not necessary for Ad-mediated DC maturation (12)(13)(14). Although capsid components of Ad vectors are thought to trigger DC maturation, the exact viral proteins involved remain controversial (15)(16)(17).…”
mentioning
confidence: 99%
“…These studies implicated the involvement of the TLR pathogen recognition system in Ad innate immune responses. While a previous study had suggested a lack of MyD88 (a critical TLR adaptor gene) dependence in the Ad-induced upregulation of CD86 in mouse dendritic cells in vitro (35), a different in vivo study found a reduction in Ad-elicited cytokines using an Ad challenge model in TLR4-deficient mice (40). Based upon these considerations we sought to further validate the transcriptome results in general through investigation of a critical TLR system adaptor gene, MyD88.…”
mentioning
confidence: 99%